Palladium catalyzed C–H bond acetoxylation: isoxazolinyl as a directing group. Issue 62 (14th June 2016) - Geng, Caiwei; Jiang, Minghui; Feng, Lifei; Jiao, Peng
Abstract : Pd(OAc)2 -catalyzed acetoxylations of 3-aryl or 3-alkyl groups mounted on a 2-isoxazoline ring were studied. Substituent effect on reactivity and regioselectivity was examined. The acetoxylation was applied to the synthesis of useful intermediates. Abstract : Pd(OAc)2 -catalyzed acetoxylations of 3-aryl or 3-alkyl groups mounted on a 2-isoxazoline ring were studied. Ortho -selective C–H bond activation directed by an isoxazolinyl group was realized. 2-Isoxazoline rings without and with one or two alkyl substituents in the 5-position were effective directing groups. The substituent effect on reactivity and regioselectivity was examined. The acetoxylation was applied to the synthesis of useful intermediates.